On the generalized Hartley-Hilbert and Fourier-Hilbert transforms - Al-Omari, Shrideh Khalaf Qasem; Kilicman, Adem (SpringerOpen, 2012)
In this paper, we discuss Hartley-Hilbert and Fourier-Hilbert transforms on a certain class of generalized functions. The extended transforms considered in this article are shown to be well-defined, one-to-one, linear and continuous mappings with respect to δ and Δ convergence. Certain theorems are also established.